Defect density associated with constituent particles in AA2024‐T3 and its role in corrosion. (26th August 2015) - Glenn, Alexander M.; Hughes, Anthony E.; Torpy, Aaron; Nolze, Gert; Birbilis, Nick
Abstract : Electron backscatter diffraction (EBSD) and scanning electron microscopy were combined to study the effect of residual defect density on corrosion initiation in aluminium alloy AA2024‐T3. EBSD was used to determine the level of misorientation (MO), from pixel to pixel, within individual grains. The MO can be determined with respect to either the average orientation angle of the grain or with respect to the average orientation angle of the surrounding pixels (in this instance, a matrix of 7 × 7 surrounding pixels has been applied). Herein, the MO, determined using the surrounding pixels, was used as the means for the assessing the level of defect density within a grain. It was found that there was a noteworthy, but not definitive, correlation of MO with corrosion initiation after 1 min exposure to 0.1 M NaCl solution. Additionally, the S and θ ‐phase particles were also identified using EBSD, displaying a range of MO and therefore defect density. Copyright © 2015 John Wiley & Sons, Ltd.